PERANCANGAN DAN ANALISIS PISAU PENGHANCUR PADA MESIN PENGHANCUR LIMBAH KACA - Machrus Ferdian; Nur Robbi; Ismi Choirotin (UNIVERSITAS ISLAM MALANG, 2022)
Waste is a problem that is often faced by countries in the world. Glass waste is one of the wastes in the disposal site, one way that can be taken to reduce glass waste is to process glass waste to become other products that are more useful such as a mixture of bricks, artwork, or converted into new glass. That's why innovations emerged to make glass waste crushing machines. Planning a crushing knife on this glass waste crushing machine uses design and analysis methods. The crushing knife consists of a blade, knife mount, disc, shaft, one blade restraint, knife restraint. The crushing knife on this glass waste crushing machine has a type of hammer mill knife. The dimensions of this crushing knife are: the width of the blade (radius) is 165.59mm, the length of the crushing knife is 310mm. The crushing knife consists of: 9 blades, 3 knife stands, 4 plates, 12 knife restraints, and 6 M12 nuts. From the destruction of light glass as much as 2kg, obtained output of 1,050kg. From the results of the destruction of light glass waste, the most dominant glass size is 1.18-2mm which is 0.3787kg (35.79%).